Sensitometric comparison of E and F dental radiographic films using manual and automatic processing systems - Dabaghi A.; Tahmasbi MJ; Karbasi N.; Tabesh H. (Tehran University of Medical Sciences, 2008)
Background and Aim: Processing conditions affect sensitometric properties of X-ray films. In this study, we aimed to evaluate the sensitometric characteristics of InSight (IP), a new F-speed film, in fresh and used processing solutions in dental office condition and compare them with Ektaspeed Plus (EP).Materials and Methods: In this experimental in vitro study, an aluminium step wedge was used to construct characteristic curves for InSight and Ektaspeed Plus films (Kodak Eastman, Rochester, USA).All films were processed in Champion solution (X-ray Iran, Tehran, Iran) both manually and automatically in a period of six days. Unexposed films of both types were processed manually and automatically to determine base plus fog density. Speed and film contrast were measured according to ISO definition. Data were analyzed using one-way ANOVA and T tests with P<0.05 as the level of significance.Results: IP was 20 to 22% faster than EP and showed to be an F-speed film when processed in automatic condition and E-F film when processed manually. Also it was F-speed in fresh solution and E-speed in old solution. IP and EP contrasts were similar in automatic processing but EP contrast was higher when processed manually. Both EP and IP films had standard values of base plus fog (<0.35) and B+F densities were decreased in old solution.Conclusion: Based on the results of this study, InSight is a F-speed film with a speed of at least 20% greater than Ektaspeed. In addition, it reduces patient exposure with no damage to image quality.